Compatibilization of polypropylene/poly(glycolic acid) blend with maleated poe/attapulgite hybrid compatibilizer: Evaluation of mechanical, thermal, rheological, and morphological characteristics. Issue 6 (19th February 2020) - Yang, Haicun; Cai, Zinan; Liu, Haotian; Cao, Zheng; Xia, Yanping; Ma, Wenzhong; Gong, Fanghong; Tao, Guoliang; Liu, Chunlin
Abstract: In this work, the compatibilization effects of hybrid maleated POE/attapulgite hybrid compatibilizer (M‐POE/ATP) on the immiscible polypropylene/poly(glycolic acid) (PP/PGA) blends was investigated. The hybrid compatibilizer integrating strengthening, toughening and compatibilization functions was prepared via one‐step reactive extrusion using peroxidated ATP as the initiator. Then, the effects of compatibilizer dosage on the mechanical, thermal, rheological and morphological characteristics of blends were evaluated in detail. It was found that the hybrid compatibilizer resulted in the significantly enhanced compatibility and mechanical performance. Increased amount of compatibilizer content fractionated and almost wholly suppressed the crystallization process of PGA. The compatibilized blends showed higher thermal stability than pure PGA, and lower storage modulus and complex viscosity at higher shearing frequency. PGA in the blends presented a much lower degradation rate, which lead to the higher strength retention of 81% for the blend with 4 wt% of compatibilizer in buffer solution after 35 days. Abstract : The maleated POE/attapulgite (M‐POE/ATP) hybrid compatibilizer was prepared via one‐step reactive extrusion using peroxidated ATP as the initiator to compatilize the immiscible polypropylene/poly(glycolic acid) (PP/PGA) blends. The effective integration of strengthening, toughening, and compatibilization functions for this compatibilizer was confirmed by the enhanced mechanical performance, improved compatibility and the transform of fractured surface morphology of blends in the presence of M‐POE/ATP.